2021
DOI: 10.21037/tp-20-224
|View full text |Cite
|
Sign up to set email alerts
|

Fetal brain issues in congenital heart disease

Abstract: Following the improvements in the clinical management of patients with congenital heart disease (CHD) and their increased survival, neurodevelopmental outcome has become an emerging priority in pediatric cardiology. Large-scale efforts have been made to protect the brain during the postnatal, surgical, and postoperative period; however, the presence of brain immaturity and injury at birth suggests in utero and peripartum disturbances. Over the past decade, there has been considerable interest and investigation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 99 publications
2
17
0
Order By: Relevance
“…Changes in cortical development have been described in fetuses with growth restriction (FGR), congenital heart defects (CHD) and non-severe ventriculomegaly. Whereas FGR, with or without pre-eclampsia, has been associated with only reduced Sylvian fissure depth 25,30,31 , fetuses with CHD 32 or isolated ventriculomegaly 24,33 have been reported to experience a widespread suboptimal cortical folding process, with shallower sulci depths and delayed operculization, similar to that observed in our ART population.…”
Section: Discussionsupporting
confidence: 81%
“…Changes in cortical development have been described in fetuses with growth restriction (FGR), congenital heart defects (CHD) and non-severe ventriculomegaly. Whereas FGR, with or without pre-eclampsia, has been associated with only reduced Sylvian fissure depth 25,30,31 , fetuses with CHD 32 or isolated ventriculomegaly 24,33 have been reported to experience a widespread suboptimal cortical folding process, with shallower sulci depths and delayed operculization, similar to that observed in our ART population.…”
Section: Discussionsupporting
confidence: 81%
“…While traditionally intraoperative factors have been regarded as the major contributing factor to NDD in CHD, recent research has suggested an opposite direction that preoperative and innate patient factors are playing more important roles [2]. This is also in accordance with the findings that in CHD patients, changes in fetal brain size and abnormalities in brain structure have been detected as early as the second trimester [4]. Overall, this suggests that neurodevelopment is disturbed in CHD but the underlying mechanisms are less understood.…”
Section: Introductionsupporting
confidence: 72%
“…Reduced exercise tolerance is also a concern and may have important functional implications ( Tran et al, 2022 ). Chronic hypoxemia is associated with long-term morbidity and late mortality, even in cases of mild desaturation ( Schafstedde et al, 2021 , Egbe et al, 2017 , Zentner et al, 2020 ), and may be an important predisposing factor for altered cerebral development, white matter (WM) injury, and subsequent cognitive functioning ( Owen et al, 2011 , Morton et al, 2017 , Limperopoulos et al, 2010 , Sun et al, 2015 , Claessens et al, 2018 , Spaeder et al, 2017 , Claessens et al, 2019 , Rajagopalan et al, 2018 , Lee et al, 2021 , Sadhwani et al, 2022 ). Significant reductions in global brain volume and subcortical gray matter (GM) volume were associated with lower SaO 2 in our adolescent and adult Fontan cohort ( Verrall et al, 2021 ), consistent with our earlier findings from adults with other forms of cyanotic CHD ( Cordina et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%